The China Path to Economic Transition and Development - Hong, Yinxing; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2016)
This book by the renowned Chinese scholar Dr. Yinxing Hong provides the reader with a perceptive analysis of what has worked in China$1 (Bs development model. Over the past 30 years, China has experienced a remarkable economic rise, but it now faces the challenge of switching the drivers of this economic growth, which have proven so successful. The path has not been an easy one, and many challenges lie ahead. However, the rise of the Chinese economy has been the most significant global development in recent years. Is there a specific Chinese model? How was the Chinese transition, from a Soviet-style economic structure to one that is more open to market influences and the global market, achieved? In 15 essays, Dr. Hong provides fascinating insights to these and other key questions. The essays cover the challenges involved in transition and how the market-oriented reforms progressed; what the consequences of the transition were for public goods provision and how China opened up its economic system. The essays in Part II address the remaining challenges facing rural areas trying to develop a more consumer-driven economic base, and how to effectively modify the model of economic development. This book provides a sound basis for policymakers and scholars alike, as well as anyone who wants to get an insider$1 (Bs view of the progress and challenges faced by China$1 (Bs economic development.s
Preface -- Foreword -- PART I: The China Model of Economic Reform and Opening -- A Theory of Transition Economics -- Economic Transition and Theoretical Innovations -- Evolutionary Market-Oriented Reform in China -- Understanding the Establishment of Market Order -- The Reform of the Public-Goods Supply System -- The Transformation of the Open-Economy Model -- PART II: The China Path of Economic Development -- Sustaining Factors for China$1 (Bs Economic Growth -- Changing the Economic Development Model -- The New Economy and the Revolution in the Mode of Production -- Developing an Innovation-Driven Economy -- Integrated Urban-Rural Development -- Modernization in Terms of China's (3z(BThree Rural Issues(3y (B-- The Consumption-Driven Economic Growth Model -- The Evolving Economic Thinking of the Communist Party of China.s
Keywords: Economic policy; Asia -- Economic conditions; Economics; Asian Economics; Economic Policy; Electronic books